Biosynthesis of silver nanoparticles from leaf extract of Litchi chinensis and its dynamic biological impact on microbial cells and human cancer cell lines - Iqbal, Muhammad Javed; Ali, Sikandar; Rashid, Umer; Kamran, Muhammad; Malik, Muhammad Faheem; Sughra, Kalsoom; Zeeshan, Nadia; Afroz, Amber; Saleem, Javaria; Saghir, Mariam (Cellular and Molecular Biology, 2018)
Green synthesis of metallic nanoparticles has attracted a great deal of attention from scientific community due to its biocompatibility and environment friendly nature. In the present study, silver nanoparticles were biologically synthesized using leave extracts of Litchi chinensis. Biosynthesized silver nanoparticles were characterized and their applications were observed by different methodologies. Bio-reduction reaction was confirmed by the surface plasmon resonance of silver nanoparticles at 417 nm through UV-VIS spectrophotometer. FTIR analysis revealed that the amine groups present in the leaf extracts were responsible for the reduction of silver ions to silver nanoparticles. X-ray diffraction analysis was used to determine the crystalline nature of silver nanoparticles and their diameter was noted in the range of 41-55 nm by scanning electron microscopy. Antibacterial activity was observed against gram positive and gram negative strains of bacteria. Furthermore, human epithelial type 2 cancer cells (HEp-2) and Human breast adenocarcinoma cells lines (MCF-7) were treated with the biosynthesized silver nanoparticles using MTT assay. The resulting cell death rate was noted up to 40.91+1.99%. This study concludes that plant mediated biosynthesis of nanoparticles is the superior alternative compared to chemical and physical approaches, to utilize them as drug delivery tool and need to conjugate apoptosis inducing biological agents with silver nanoparticles to suppress the uncontrolled division of cancer cells.